ADVANCED MANUFACTURING FOR NUCLEAR CORE DESIGN - Betzler B. R.; Ade B. J.; Wysocki A. J.; Greenwood M. S.; Heineman J. J. W.; Chesser P. C.; Jain P. K.; Heidet F.; Bergeron A. (EPJ Web of Conferences, 2021)
Advanced manufacturing has the potential to revitalize US manufacturing, with valuable applications in several industries, including aerospace, automotive, and construction. Some of these applications have clear-cut objectives (e.g., maintain component performance while reducing mass). Applications of advanced manufacturing of nuclear components have aimed at recapturing lost manufacturing capabilities or addressing maintenance of legacy reactor components. Through the Department of Energy, Office of Nuclear Energy, Transformational Challenge Reactor design and analysis thrust, applications of advanced manufacturing, in particular, additive manufacturing, to core design has yielded reactor designs that are free from conventional manufacturing constraints. For applications in core design, the multiphysics nature of the key core metrics (e.g., peak temperature, peak power) in addition to transient safety performance requirements provides a more complex set of objectives that requires more advanced modeling and simulation tools. Additive manufacturing provides high dimensional control and design flexibility to produce complex coolant channel shapes for improved heat transfer properties and low peak material temperatures. Additional mechanisms for improved heat transfer characteristics and temperature-controlled feedback mechanisms have also been explored and incorporated into designs. While some of these enhancements are not directly beneficial for the current operating pressurized water reactor fleet, benefits may be realized in specific reactor applications that have a more constrained design space (e.g., mass, size, material type) or design metrics (e.g., fuel utilization).